Urban trees left high and dry – Modelling urban trees water supply and evapotranspiration under drought - Kluge, Björn; Kirmaier, Margit (Environmental Research Communications, 2024)
Long-lasting extreme weather conditions are expected to occur more frequently in the future owing to climate change, as demonstrated by the recent heat waves. In particular, the decrease in precipitation during the summer months had a significant impact on urban tree water availability. Therefore, it is imperative to develop methodologies for determining the available water supply and evapotranspiration rates for urban trees. We mapped data from 49 urban small-leaved linden trees with varying characteristics including groundwater levels, shading situations, tree pit sizes, pavement materials, and sealing ratios. By combining these data with an adapted Penman-Monteith method to calculate evapotranspiration, we simulated the soil water storage and evapotranspiration rates of these trees during the very dry year of 2018 as an example. Model validations were performed using lysimeter and sap-flow studies on Tilia cordata trees in 2022. During the growing season, most trees experienced water stress on > 85% of the days because of weak precipitation events that failed to refill soil water storage. In contrast, trees with additional water supply through capillary rise reached water stress approximately 45 days later. The model results suggest that many trees will require additional water supply during predicted droughts in the future, which could have significant implications for urban forestry management. This model approach can be used to test and refine future water supply management strategies, making it a useful planning tool for improving the water efficiency of trees in urban areas and blue-green infrastructure.